Unraveling Learning Difficulties in Biology Among Class VIII Students at SMP Negeri 19 Palu - Eka Hardiyanti R. Batania; Musdalifah Nurdin; Amalia Buntu (CV. Dharma Samakta Edukhatulistiwa, 2025)
This research aims to identify the learning difficulties of 8th-grade students in Science (Biology) at SMP Negeri 19 Palu. This type of research is descriptive. The subjects in this research were all students of classes VIII A and VIII B, consisting of 46 students. The data collection technique used was a questionnaire on factors influencing students' learning difficulties. The results of the study showed that the average internal difficulty factor for the